Screen-vision: um panorama sobre a evolucao visual da tecnologia do video - Labuto Junior, Alberto (2014)
In the age of digital communication, video has increasing importance, both as a technological tool, such as audiovisual language. From this context, we analyzed the evolutionary process of visual technologies leading to the emergence and popularization of video technology. We begin with an analysis on the physiological aspects of vision. The mechanics of vision, with light as optical stimulator through which we see the world. The goal is to understand the organic process that originates the phenomena of color and form in motion into the mind, as a starting point for a systemic approach to vision, in order to understand the evolutionary path of the technology, wich starts from the study of human vision to vision design of the cyborg. Then, a view of the historical evolution of visual languages, from the visual emergence of first symbols to advent of video, seeking the understanding of the process that led to an evolution in visual communication towards the collectivity of information, with peak in television and video expanded in new media. Finally, an overview of the vision design of the cyborg, in a context where, as a result of a constant evolution, video technology becomes sufficiently intimate and reliable while we adapt to its full-time use, mounting or even implementing electronic devices in our body to expand the vision